The Philosophy of Quranic Meaning: A Reconstruction of Al-Raghib al-Isfahani’s Lexical-Semantic Methodology - Alan Saputra; Diyah Pratiwi; Abdul Matin Bin Salman (al-Afkar, Journal For Islamic Studies, 2026)
Qur'anic semantics, as a branch of the philosophy of language, plays a crucial role in unraveling the issues of polysemy (al-wujuh wa al-naza'ir) and shifts in textual meaning. This article comprehensively reconstructs the philosophy of meaning and semantic methodology of Abu al-Qasim al-Raghib al-Asfahani (d. 1108 CE) as presented in his monumental work, Mufradat Alfaz Al-Qur'an. The analysis focuses on the concept of iman (faith) as a case study to examine the application of classical linguistic realism theory. The research employs a qualitative, descriptive-analytical method based on library research, utilizing a classical linguistic epistemology approach. The findings indicate that: (1) Raghib constructs an epistemology of meaning grounded in linguistic realism, wherein meaning is inherent and substantial within the root word (al-wadʼ al-lughawi); (2) Regarding the concept of iman, Raghib integrates the etymological linguistic meaning derived from the root a-m-n, signifying tranquility and freedom from fear into a hierarchical theological structure comprising tasdiq bi al-qalb (assent of the heart), iqrar bi al-lisan (verbal confession), and 'amal bi al-arkan (enactment through deeds); (3) Raghib’s methodology successfully resolves the dichotomy between faith and deeds that challenged classical theologians. This reconstruction offers a robust theoretical and methodological contribution to the development of contemporary thematic exegesis (tafsir mawdu'i) and provides an inclusive, systemic resolution for addressing modern radicalism and secularism.